Emergent techno-environmental phenomena - Hadfield, Linda (Cranfield University, 1997)
Environmental problems, and human attempts to manage them, can be conceptualised as evolutionary complex systems, involving interlinked processes of physical, knowledge, technological, institutional, perceptual and behavioural change. Issues such as traffic pollution and asthma may be viewed as emergent systems, embedded within overlapping hierarchical systems. A distinction may be made beween changes in physical systems (“physical emergence”), changes in human knowledge about those systems (“knowledge emergence”) and changes in human perceptions (“perceptual emergence”). While processes of physical and knowledge emergence are important, it is through perceptual emergence that a phenomenon comes to be regarded as a “problem” or “issue”, potentially leading to changes in policy, institutional arrangements or behaviour. Physical changes may have impacts on human beings, which may be measurable and predictable in the mass. However, the outcome of such an impact, from the point of view of a particular individual, is mediated by that individual’s perception, which is dictated by his or her personal experience, understanding and interests (“appreciative system”). These perceptions in turn will determine the individual’s behaviour, which may feed back into the collective appreciative system, policy system, and the base physical system. The distinction between policy based on measurement and control of impacts and individual perceptions and behaviour dependent on outcomes leads to incongruity between the “institutional” and “individual” views of an issue. The thesis investigates this incongruity in the case of the “traffic pollution and asthma” emergent system. The perceptions of “institutional” and “individual” actors involved in the system were elicited by means of unstructured and semi-structured interviews, and analysed in terms of a number of key concepts (perceptions of measurement, risk and spatiality) across a number of dimensions (different actors in the same location, the same hierarchical position in different locations, and between a specific institution and individuals). The empirical investigation demonstrates differences between multiple institutions managing different aspects of the problem and a lack of understanding and communication between institutions and individuals, despite the fact that an expressed aim of policy in this area is directed at communicating with individuals with the intention of changing individual behaviour.